Creep of calcareous sand in Tunisia: effect of particle breakage at low stress level - Hyunwook Choo; Minhyuk Kwon; Lamia Touiti; Young-Hoon Jung (International Journal of Geo-Engineering, 2020)
Abstract Aims/hypothesis One of the critical mechanisms determining creep in granular materials is the breakage of soil particles. This study aims at evaluating the time-dependent creep deformation of calcareous sand at low effective stress conditions. Methods K0 creep tests were performed for both calcareous and silica sands at low stresses of 65 and 120 kPa, and the results of creep tests were compared with the results of constant rate of strain (CRS) tests at high stress levels up to 12 MPa. For a quantitative evaluation of the effect of the particle breakage on the creep deformation of calcareous sand, the relative breakage ( $$B_{r}$$ B r ) was determined based on the results of sieve analyses. Results The results demonstrate that Tunisia calcareous sand experiences significant particle breakage during creep and the consequent creep deformation at low stress level. The determined $$B_{r}$$ B r after creep at low stress level is comparable with that after the CRS test at high stress level. Conclusions High potential of particle breakage inherited by characteristic minerology of the calcareous Tunisia sand significantly influences the creep deformation at low stress level.